2011
DOI: 10.1371/journal.pgen.1001344
|View full text |Cite
|
Sign up to set email alerts
|

Viral Genome Segmentation Can Result from a Trade-Off between Genetic Content and Particle Stability

Abstract: The evolutionary benefit of viral genome segmentation is a classical, yet unsolved question in evolutionary biology and RNA genetics. Theoretical studies anticipated that replication of shorter RNA segments could provide a replicative advantage over standard size genomes. However, this question has remained elusive to experimentalists because of the lack of a proper viral model system. Here we present a study with a stable segmented bipartite RNA virus and its ancestor non-segmented counterpart, in an identica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
105
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 32 publications
1
105
1
Order By: Relevance
“…This may not be a problem in the above experimental set-up at high MOI, but in order for a segmented genome to persist for long evolutionary periods, a direct benefit of segmentation should exist that overcomes this penalty. Ojosnegros et al [30] explored potential mechanisms providing such advantage to the segmented D417/D999 virus in comparison with the standard FMDV one. After ruling out differences in RNA replication rates and protein expression, the authors concluded that a higher stability of viral particles containing the shorter genomes could provide the required fitness advantage [30].…”
Section: Evolution Of Genome Architecture: the Rise Of Segmented Genomesmentioning
confidence: 99%
See 1 more Smart Citation
“…This may not be a problem in the above experimental set-up at high MOI, but in order for a segmented genome to persist for long evolutionary periods, a direct benefit of segmentation should exist that overcomes this penalty. Ojosnegros et al [30] explored potential mechanisms providing such advantage to the segmented D417/D999 virus in comparison with the standard FMDV one. After ruling out differences in RNA replication rates and protein expression, the authors concluded that a higher stability of viral particles containing the shorter genomes could provide the required fitness advantage [30].…”
Section: Evolution Of Genome Architecture: the Rise Of Segmented Genomesmentioning
confidence: 99%
“…Ojosnegros et al [30] explored potential mechanisms providing such advantage to the segmented D417/D999 virus in comparison with the standard FMDV one. After ruling out differences in RNA replication rates and protein expression, the authors concluded that a higher stability of viral particles containing the shorter genomes could provide the required fitness advantage [30]. In this sense, genome segmentation may provide a molecular mechanism to overcome the trade-off between genome size and particle stability, as it allows increases in the amount of genetic information encoded by the complementing genomes as a whole while relaxing packaging constraints for each individual segment.…”
Section: Evolution Of Genome Architecture: the Rise Of Segmented Genomesmentioning
confidence: 99%
“…per cell; for each passage 2Â10 6 BHK-21 cells were infected with the virus contained in 200 µl of the supernatant from the previous infection, which included 2Â10 7 -4Â10 7 p.f.u.) (García-Arriaza et al, 2004Ojosnegros et al, 2011). The Genbank accession numbers for the viral genomes used in the present study are AJ133357 (C-S8c1), DQ409183 (D417ev) and DQ409184 (D999ev).…”
Section: Methodsmentioning
confidence: 99%
“…The basis of this evolutionary transition was the extensive exploration of sequence space by the standard virus that reached a point at which the segmented versions displayed higher replicative fitness than the unsegmented parental genome (Moreno et al, 2014). Once the critical genetic event occurred, the selective advantage of the bipartite virus was reinforced by enhanced stability of the virions that encapsidated shorter genomes (Ojosnegros et al, 2011). Evidence that infectivity was dependent on complementation includes: (i) presence of genomes with the expected deletions with undetectable levels of standard RNA in individual viral plaques (García-Arriaza et al, 2004); (ii) two-hit kinetics for plaque formation (García-Arriaza et al, 2004;Manrubia et al, 2006); (iii) reconstruction of the complementation system by co-transfection with DRNAs transcribed from plasmids encoding FMDV RNA with the corresponding deletions (García-Arriaza et al, 2004); (iv) evidence that L protein plays a major role in proteolytic events that are associated with the complementation (Moreno et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Another potential cost of genome segmentation would be the breakage of co-adapted groups of genes during coinfection with several strains of the virus 10 . Several advantages have been proposed to compensate for these costs: (i) for the high mutation rates of most RNA viruses, smaller segments are more likely to be copied without errors than larger segments 11 , (ii) smaller genomic segments should be replicated faster 12 , (iii) segmentation favors genomic reassortment and thus increases genetic variability by rapidly bringing together beneficial mutations that have occurred in different lineages 13,14 , minimizing the effect of clonal interference 15 and speeding up the rate of adaptation, (iv) encapsidation of smaller genomes results in enhanced capsid stability 16 , (v) particularly in the case of plant viruses, smaller capsids would facilitate trafficking throughout the size-limiting plasmodesmata 17 , and (vi) segmentation represents an efficient yet simple way to control gene expression by regulating gene copy numbers 18 .…”
mentioning
confidence: 99%